Optimizing ATR inhibition and Cisplatin Synergy in Ewing Sarcoma - Ohmura, Shunya; Grünewald, Thomas G. P. (Clinical cancer research, 2024)
EWSR1::FLI1-mediated dysregulation of cellular machinery opens up potential new avenues for Ewing sarcoma treatment. A recent study demonstrates that pharmacologic ATR kinase inhibition dramatically synergizes with low-dose cisplatin through EWSR1::FLI1-dependent rewiring of transcription, DNA repair, and translation machinery, which could maximize the therapeutic window of the combinatory therapy.
Gesehen am 09.10.2024